PELATIHAN MEMBACA PUISI PADA ANAK-ANAK DI DESA PARINGGONAN KECAMATAN ULU BARUMUN - Herawati Parapat, Lili; Huda, Rahmat; Jariah, Ainun; Intan Lestari, Tri (Martabe : Jurnal Pengabdian Kepada Masyarakat, 2021)
This community service on poetry reading training for children in Paringgonan village aims to instill art in children. Cultivate the soul to become a human being who has sympathy for sesame. Appreciating beauty, appreciating literary works. Introducing literary works to children is considered to have a beneficial effect in growing children's character to become insecure, responsible, and others. Poetry reading training is carried out directly. Because the method used is direct practice (demonstration). participants found 10 children whose homes are close to the training site. Study for 3 months. This training has an impact on the children. They are very quick to be good at reading poetry directly